Analyzing the coalition factor among actors in NWRP formulation rocess / Junaida Ismail and Siti Zuliha Razali - Ismail, Junaida; Razali, Siti Zuliha (2019)
Policy formulation refers to the process of formulating, or drafting, an acceptable course of action for the selected policy agenda. Ideally, the objective of policy formulation is to resolve the problems of society. The issue of water in Malaysia is considered as its own problem that needs to be assessed by the government. Water is considered one of the most important national resources, but at the same time, it is scarce. Therefore, water as a resource needs to be planned for, developed, conserved and managed properly by both the Federal Government and State Government for the usage and benefits of society. The Malaysian government needs to have its own policies for water resources in order to secure the governance of water resources and to balance the existing and future water policies under the jurisdiction of various government bodies. In April 2010, the idea of having our own National Water Resource Policy was mentioned by the deputy minister Tan Sri Joseph Kurup (http://borneopostonline, April 2010). With that, The NWRP draft was first presented in the meeting of Mesyuarat Sumber Air Negara (MSAN) on 6 October 2011 and subsequently approved by the Member of Parliaments (MPs) on 22 February 2012. The policy was then launched on 24 March 2012. The main purpose of NWRP is to clearly indicate the obligations of the Federal and State governments in water resource management. This policy differs from the existing enacted Acts under SPAN, namely Act 654 and Act 655, which exclusively focus on water services in Malaysia. Unlike these previous Acts, NWRP focuses on water resource management. Furthermore, the formulation of NWRP itself stresses on the significance of water resources for this country and the need to manage water resources based on integrated water resource management. As encapsulated in the Tenth Malaysian Plan (2011-2015), the sustainability of water resources was highlighted as an important issue. The process of formulating NWRP considered three main sustainable principles. Principles of National Water Resources Policy Principles of NWRP Description Water resources security water resources must be secured to ensure its readiness to meet the needs and demands of both man and nature through utilizations of its potential and minimization of its damaging impact.